2006
DOI: 10.1007/s10600-006-0207-2
|View full text |Cite
|
Sign up to set email alerts
|

Volatile constituents of flowers and leaves of Anthemis hyalina

Abstract: 546.913The chemical composition of the essential oils of the flowers and leaves of Anthemis hyalina were analyzed by GC and GC-MS for the first time. The oils were found to contain seventy-two components. cis-Chrysanthenyl acetate (14.9% and 17.8%), camphor (11.6% and 1.7%), terpinen-4-ol (8.3% and 1.2%), germacrene-D (5.1% and 2.1%), β-caryophyllene (4.1% and 5.4%), myrcene (3.6% and 16.9%), bicyclogermacrene (3.5% and 0.9%), α-pinene (2.3% and 4.1%), cis-β-ocimene (2.1% and 4.3%) and isospathulenol (0.4% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The chemical composition of the essential oils from several Anthemis species such as A. carpatica 8 20 have been studied and the authors reported that variation in the yield and chemical composition of essential oils are usually affected by period of collection, regions, the environmental condition and part of plants.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of the essential oils from several Anthemis species such as A. carpatica 8 20 have been studied and the authors reported that variation in the yield and chemical composition of essential oils are usually affected by period of collection, regions, the environmental condition and part of plants.…”
Section: Introductionmentioning
confidence: 99%
“…parnassica [ 21 ], A. hyalina DC. [ 22 ], A. tinctoria L. [ 23 ], A. cretica L. ssp. leucanthemoides (Boiss.)…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of the essential oils and the chemotypes of several Anthemis and chamomile species from different countries have been extensively studied and reported [11][12][13][14][15][16][17][18][19]. However, very few studies have been reported on Moroccan C. mixtus essential oils.…”
mentioning
confidence: 99%